Perlindungan Hukum Bagi Debitor Terhadap Pelaksanaan Rencana Perdamaian Penundaan Kewajiban Pembayaran Utang Akibat Pandemi Covid-19 - Neysa Tania; Dixon Sanjaya; Jason Novienco (Nagari Law Review, 2021)
The Covid-19 pandemic has had a negative impact on business in various sectors and is one of the factors that causes the high number of filings for Bankruptcy cases in the Commercial Court. To prevent this, Law Number 37 of 2004 on Bankruptcy & Suspension of Debt Payment Obligation provides an opportunity for debtors to apply for suspension of debt payment as an opportunity to pay off their debts. However, in the process of determining the status of the application for suspension of debt payment obligations until the settlement plan for the suspension of debt payment obligations has been homologated, Law Number 37 of 2004 on Bankruptcy & Suspension of Debt Payment Obligation still provides room for creditors with bad faith to cause disadvantages towards the debtor. Therefore, in this paper, the author examines how the legal protection for debtors on the implementation of the suspension of debt payment's peace agreement that is affected by Covid-19. The results show that there is still inadequate legal protection for debtors against suspension of debt payment's peace agreement affected by Covid-19 due to the lack of provisions that can protect debtors in the bankruptcy law and suspension of debt payment obligations